Constipation in multiple system atrophy: a pilot study in Chinese patients - Chen, Yalan; Huang, Hongyan; Zhang, Peng; Xu, Yanming; Chen, Yangmei (Frontiers in Neurology, 2023)
Objective This study aimed to investigate the prevalence and clinical characteristics of subjective constipation in Chinese patients with multiple system atrophy (MSA), as well as the timing of constipation onset relative to the occurrence of motor symptoms. Methods A total of 200 patients who were consecutively admitted to two large Chinese hospitals from February 2016 to June 2021 and subsequently diagnosed with probable MSA were enrolled in this cross-sectional study. Demographic and constipation-related clinical data were collected, and motor and non-motor symptoms were assessed using various scales and questionnaires. Subjective constipation was defined using ROME III criteria. Results The frequency of constipation was 53.5, 59.7, and 39.3% in MSA, MSA with predominately parkinsonism (MSA-P), and MSA with predominately cerebellar ataxia (MSA-C), respectively. MSA-P subtype and high total UMSARS scores were associated with constipation in MSA. Similarly, the high total UMSARS scores were associated with constipation in MSA-P and MSA-C patients. Among the 107 patients with constipation, 59.8% began experiencing it before the onset of motor symptoms, and the interval between constipation and occurrence of motor symptoms was significantly longer in these patients than in those who experienced constipation after onset of motor symptoms. Conclusion Constipation is a highly prevalent non-motor symptom in MSA and more often occurs before the onset of motor symptoms. The results of this study may help guide future research into MSA pathogenesis in its earliest stages.